Analisis Manajemen Sumber Daya Insani - Adib Khusnul Rois; Suprianto Suprianto (Universitas Muhammadiyah Ponorogo, 2021)
Management is a process in order to achieve goals by working together through people and other organizational resources. Human Resources are the determinants of the success of zakat management, humans are creatures that have various potentials in themselves, Human Resources are the basis of human nature until humans really spawn their minds and minds to become creatures that can produce in development. Human Resources (SDI) is the basic capital in the national development process. Therefore, the quality of resources must always be developed and directed in order to achieve the expected goals. This balance can occur by humanizing humans. BAZNAS is an institution that has been structured in law and has a standard legal basis, there are several principles that must be adhered to in implementing Human Resources management in BAZNAS including Human Resource Planning, Human Resource Planning, Qualified or Professional Human Resources, Placement, and Human Resources Recruitment.